ASSISTÊNCIA DE ENFERMAGEM NO PRÉ-NATAL A MULHERES PRIVADAS DE LIBERDADE: UMA REVISÃO INTEGRATIVA (REMUNOM, 2025)
This study aims to analyze the scientific evidence available in the literature on the role of nursing in prenatal care for women deprived of liberty. This is an integrative review conducted by searching national and international databases. Studies published in recent years that address the practices, challenges, and contributions of nursing in the health care of pregnant women in prison were selected. The results highlight gaps in care, structural difficulties in prisons, and the importance of ethical and humane work by nursing professionals. It is concluded that there is a need to strengthen public policies and training of professionals to ensure quality prenatal care for this vulnerable group.Keywords: Nursing; Prenatal care; Women in prison; Women's health; Integrative review.